'Being there' is what matters: Methodological and ethical challenges when undertaking research on the outdoor environment with older people during and beyond the COVID-19 pandemic - Caroline Pearce; Sara Tilley; Catharine Ward Thompson (Elsevier, 2023)
This paper reflects on adapting research methods and processes during the COVID-19 pandemic, drawing on our experiences of conducting research on the outdoor environment with older people (aged 50+) living in Scotland. First, we discuss the challenges to the organisation of research experienced in the context of changing government and university guidelines and managing delays to planned research timelines. The shift toward remote methods stimulated by the pandemic transformed traditional notions of the research field. We consider some of the implications of this for outdoor environment research, grounded as it is on exploring the interaction between people and the places they are embedded within. Further, despite a growth of literature highlighting the benefits of remote research, we found uses for digital and online approaches limited when working with older people. Second, we reflect on whether research with older people in the context of a pandemic can be conducted ethically. Drawing on our research we describe how developing an 'ethics of care' included negotiating with formal ethics processes but also the relational, situated ethics of qualitative health research that, because of the pandemic, had begun to shift in new ways. We describe the often intangible impacts of COVID-19 such as social isolation and bereavement that we uncovered as researchers entering into the lives of older people. In closing, we outline some of the key lessons learnt from conducting research on outdoor environments with older people to enable future qualitative health research during and beyond the pandemic.